Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1529-8817.2007.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the tetrasporophyte of Asparagopsis armata (Bonnemaisoniales) limited by inorganic carbon in integrated aquaculture?1

Abstract: Seaweeds cultivated in traditional land-based tank systems usually grow under carbon-limited conditions and consequently have low production rates, if no costly artificial source of inorganic carbon is supplied. In integrated aquaculture, the fish effluents provide an extra source of dissolved inorganic carbon (DIC) to seaweeds due to fish respiration. To evaluate if the tetrasporophyte of Asparagopsis armata (Harv.) F. Schmitz (the Falkenbergia stage) is carbon limited when cultivated with effluents of a fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…armata in this system needs at least three to four effluent exchanges per hour to maintain daily saturating levels of CO 2 for photosynthesis and biomass production (Mata et al 2007). U. rigida on the other hand, after depleting the CO 2 , still has the ability to use HCO 3 − from the DIC pool (Beer 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…armata in this system needs at least three to four effluent exchanges per hour to maintain daily saturating levels of CO 2 for photosynthesis and biomass production (Mata et al 2007). U. rigida on the other hand, after depleting the CO 2 , still has the ability to use HCO 3 − from the DIC pool (Beer 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In flow-through integrated aquaculture systems, it is crucial to use relatively high effluent renewal rates to supply the algae cultures with non-limiting nitrogen and carbon levels. This allows attaining the best performance by species depending almost exclusively on CO 2 from the dissolved inorganic carbon (DIC) pool for their photosynthesis, such as A. armata (Mata et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…N supply influences the protein and pigment contents, and the C uptake rate in many types of seaweeds, including the genus Ulva (Gómez-Pinchetti et al 1998). Seaweeds under HNS from fishpond effluents benefit not only from a rich source of ammonia but also from an important and free source of dissolved inorganic C (DIC) coming from fish respiration that becomes available for algal photosynthesis (Mata et al 2007 of Ulva may also be related to high DOC excretion, which Gordillo et al (2003) reported in Ulva that was subjected to increased CO 2. Organic C release has been suggested as an effective mechanism of maintaining the C and N balance in algae in response to low CO 2 levels, although it was an inefficient response to N limitation (Gordillo et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tanks stocked with Asparagopsis were supplied with fish farm effluents and the optimal cultivation conditions were established (Mata et al , 2007. The production rates obtained were the highest reported so far for land-based cultivated algae in the scientific literature (Mata et al 2010).…”
Section: Introductionmentioning
confidence: 99%